2000
DOI: 10.1021/jp0009498
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Surface Structure and Reactivity of Pyrite:  Introducing a Potential Model for FeS2

Abstract: Atomistic simulation techniques are used to investigate the surface structure, stability and reactivity of pyrite. We introduce a potential model for FeS2 which reproduces experimental structural parameters, elastic constants and hydration energies of pyrite. We modeled the {100}, {110}, and {111} surfaces of pyrite and calculated the {100} surface to be the most stable and to show little surface relaxation, in agreement with experiment. The surfaces were hydrated by associative adsorption of water molecules w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 33 publications
(51 reference statements)
5
52
2
Order By: Relevance
“…[16][17][18] Pyrite itself has received much attention from computational methods, including DFT [19][20][21] and interatomic potential based studies. 22 In contrast, theoretical studies involving the marcasite phase are very limited, with one study comparing the thermodynamics of arsenic incorporation into pyrite and marcasite. 23 The majority of DFT studies to date have only focused on one polymorph of this mineral, thereby avoiding the difficult issue of the relative phase stability of two very similar structures.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Pyrite itself has received much attention from computational methods, including DFT [19][20][21] and interatomic potential based studies. 22 In contrast, theoretical studies involving the marcasite phase are very limited, with one study comparing the thermodynamics of arsenic incorporation into pyrite and marcasite. 23 The majority of DFT studies to date have only focused on one polymorph of this mineral, thereby avoiding the difficult issue of the relative phase stability of two very similar structures.…”
Section: Methodsmentioning
confidence: 99%
“…12 As the Buckingham potential for Fe-O interaction is purely repulsive and at the same time the code required the presence of an attractive term, the fit was performed in such a way as to correctly reproduce the Buckingham curve in the region of the onset of repulsion in order to be able to determine the distance of the water molecules from the iron atoms at the pyrite surface. The attractive part of the Lennard-Jones potential was made as small as possible, which resulted in the increase of parameter for iron.…”
Section: Description Of the Model And Simulation Methodologymentioning
confidence: 99%
“…12 A crystal slab of 200ϫ200ϫ100 lattice periods was used for the summation of the Madelung-type electrostatic contribution to the energy. The Buckingham potentials are softer then the Lennard-Jones types in the region of repulsion.…”
Section: Description Of the Model And Simulation Methodologymentioning
confidence: 99%
“…Molecular dynamics computer simulations of the interface between water molecules and a (001) pyrite surface (Philpott et al, 2004) showed that water molecules do not desorb in the temperature range 225-425 • C. In addition, the molecules are found to be attached via their oxygen atom, O wat , to an iron atom and via only one (Philpott et al, 2004) or both (de Leeuw et al, 2000) of the hydrogen atoms, H wat , to sulfur atoms of this pyrite surface. The formation of a shorter and a longer hydrogen bond with surface sulfur atoms was also confirmed by ab initio molecular dynamics of monolayer systems (Stirling et al, 2003b), which in addition established the existence of hydrogen bonds between the adsorbed water molecules themselves, see also Ref.…”
Section: Introductionmentioning
confidence: 96%